Determining factors in the adoption of corporate social responsibility practices: a sectoral analysis of mexican franchises (2019)
This article investigates the practices of corporate social responsibility (CSR) in the food, commerce and specialized services sectors of 366 franchise systems operating in Mexico. Research variables were supported in resource-based theory and agency theory. To contrast the hypotheses, the techniques of discriminant analysis and logistic regression have been used as complementary. The results conclude that the discriminatory power of organizational factors on the adoption of CSR practices influences differently in each sector. The variables size, franchise age and royalties showed greater discriminatory power in the adoption of CSR practices in the food sector; the entry fee, franchise age and percentage in the trade sector. Only the variable entry fee showed discriminant power in the specialized services sector.